KONSELING PANTI ASUHAN DALAM MENGATASI PENYIMPANGAN PERILAKU ANAK DI PANTI ASUHAN AL-JIHAD SURABAYA (Jurnal Bimbingan dan Konseling Islam, 2015)
This written examine what’s deviation type’s ari happening at Al-Jihad orpharage in Surabaya. How carrying out of guidance process and conseling to resist behaviour deviation of orpharage childern’s at Al-Jihad and How guidance result and conseling to resist behaviour deviation of orpharage childern’s at Al-Jihad. Defiation type’s which often happening are not discipline / not praying together, lie, ghoshob, and thief. Carrying out of guidence process throught a few measure’s, First, making organization struktur where one of orpharage childern’s become program guarantor.  Second, making regulations and punishment for fender. That measure’s are shaped throught group conseling to solve deviation problem’s are happening at orpharage. The result show that clien experience attitude movement be better than before conseling process have not create. This successful is ruled by 75% of percentage standard qualitative test and is categoried enough successful.